Taking Stock: A Visual Analysis of Gendered Ageing. Issue 5 (22nd May 2015) - Pritchard, Katrina; Whiting, Rebecca; Riach, Kathleen; Loretto, Wendy; Krekula, Clary
<x xml:space="preserve">Abstract</x> While various forms of imagery have been highlighted as central to processes of social construction, the potential of visual methodologies to generate insight into gendered ageing has yet to be fully exploited. We build on the developing body of visual analyses within work and organization studies to suggest how understandings of gendered ageing are impacted by our consumption of work‐related images, empirically explored here using stock photographs. We examine images of men and women of various ages to unpack the visual construction of gendered ageing within online news media, a critical context within the new economy. Through our own analysis, and our review of participants' responses to three images, we contribute to the unpacking of culturally produced age‐sensitive subject positions through examination of the interrelationships between gender, age and employment. These combined methodologies offer new insights into ways in which understandings of gendered ageing are both (visually) constructed and interpreted.